2005
DOI: 10.1143/jjap.44.5296
|View full text |Cite
|
Sign up to set email alerts
|

Au Alloy Formation with Sn–Pb or Sn–Zn Solder Nanoparticles

Abstract: Structures of simultaneously evaporated Sn-Pb and Sn-Zn nanoparticles on amorphous carbon surfaces have been elucidated using a transmission electron microscope. Spontaneous alloy formations by the deposition of Au have been observed at room temperature on a clean particle surface. AuSn 2 , Au 3 Zn and AuPb 2 ordered alloys have predominantly been produced. It was also shown that the spontaneous formation of oxide film with the thickness of 5.0 nm order upon exposure to air prevents the alloy formation even wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Also, no oxide layer is observed around the nanoparticles indicating that the surfactant/stabilizing agent has successfully prevented the Au-Sn ANPs from oxidation which is further validated by XRD. The peaks typically associated with gold or tin oxide [19] are not present in the XRD data. Yasuda et al [20] observed the formation of two phases in individual ANPs by in situ TEM for particles at or above 10 nm as expected from the phase diagram.…”
Section: Resultsmentioning
confidence: 95%
“…Also, no oxide layer is observed around the nanoparticles indicating that the surfactant/stabilizing agent has successfully prevented the Au-Sn ANPs from oxidation which is further validated by XRD. The peaks typically associated with gold or tin oxide [19] are not present in the XRD data. Yasuda et al [20] observed the formation of two phases in individual ANPs by in situ TEM for particles at or above 10 nm as expected from the phase diagram.…”
Section: Resultsmentioning
confidence: 95%
“…Alloys in the form of micro-/nanoparticles may exhibit superior properties over bulk alloys while changes in their compositions may fine-tune their attributes. 3 Binary and ternary alloy nanoparticles were investigated for basic research, such as the study of the size effect on the stability and reactivity of nanoparticles, [4][5][6] as-well-as for possible applications. Binary alloy nanoparticles are used for the formation of semiconductor nanowires, and their properties are intensely investigated as they provide the basis for tailoring vapor-liquid-solid growth to achieve complex one-dimensional material geometries.…”
Section: Introductionmentioning
confidence: 99%